Agricultural nonpoint source pollution in urban agricultural areas: An assessment system and mitigation methods. Issue 2 (7th February 2021) - Wang, Ya'nan; Shui, Wei
Abstract: With rapid urbanization, the negative external effects of urban agriculture have been gradually highlighted. A quantitative description of environmental loss is the precondition of environmental pollution control. Meanwhile, the scenario analysis settings based on model simulation and different control schemes have guiding significance for mitigating the current status of agricultural non-point source pollution (ANSP). In this study, we choose the Jinjiang River basin as the study area, and the denitrification decomposition (DNDC) model was used to simulate the nitrogen cycle in the paddy ecosystem and the revised universal soil loss equation (RUSLE) model was used with a nitrogen pollution load to construct the framework of risk assessment in agricultural nonpoint source pollution in ANSP. In addition, the best management practice (BMP) of agricultural nonpoint source pollution control was discussed. Our results are as follows: (1) The average annual soil erosion is 3161 t/km 2, which equates to moderate erosion. The average value of the nitrogen pollution load is 0.33 t/hm 2, and the total nitrogen loss load in the catchment is 1.66 × 10 5 t/a. High-level risks are distributed on both sides of the river system. (2) Based on the scenario simulation of continuous cropping using traditional management practices (TMPs), the average loss of nitrogen leaching in 2030 is 67.74% higher than in 2017. (3) A comprehensive BMP with regional differences is proposed. Under the premise of guaranteeing the amount of nitrogen absorbed by crops, this scheme can reduce the nitrogen loss by about 40.72% in 2030. The current status of ANSP cannot be underestimated. Reasonable and differentiated measures to improve agricultural management can effectively alleviate the risks of nitrogen leaching from farmland.